Internet of Things in Smart City Santiago - Soto-Gomez, J; Serey-Araneda, J; Fuentealba-Cid, D (Institute of Electrical and Electronics Engineers Inc., 2020)
Smart City Santiago seeks to solve the main problems faced by Santiago daily, thus achieving that people improve their quality of life. This model is based on the Smart City Málaga model, Spain. In the study, the main challenges facing this type of companies are presented, in term of IoT for the construction of a Smart City. The research focuses on the components that define the IoT of the referential model, such as: sensors, networks and value chain management. The methodology that is applied is exploratory, through a case study that identifies the main challenges presented by Smart City Santiago companies that use IoT in the implementation and development of a Smart City model. This is carried out with interviews with twelve companies participating in the Smart City Santiago project, which allows determining the most important challenges within each component. The results of this research contribute to companies that have an interest, collaborate or intervene in the implementation and development of the model of a Smart City. © 2020 IEEE.
Keywords: IoT; Smart City; technological field